HISTORY OF COMPOSITE MATERIALS AND THEIR ROLE IN THE MODERN WORLD - Mengliyeva , Anora (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This thesis analyzes the historical development of composite materials and their role and significance in modern engineering from ancient times to the present day. It highlights the evolution from the earliest composite materials used in ancient civilizations to modern polymer, metal, and fiber-reinforced composites.The study also examines natural and artificial composite materials, their structure, properties, and fields of application. The importance of composite materials in modern industry, particularly in aviation, automotive manufacturing, and construction, is substantiated through their light weight, high strength, and contribution to energy efficiency. In addition, trends and prospects in the development of the composite materials market are analyzed. The research findings demonstrate that composite materials are increasingly becoming a viable alternative to traditional materials in the future.